+0  
 
0
296
2
avatar+2509 

Help.

NotSoSmart  Apr 11, 2017
 #1
avatar+7153 
+3

a.

The center of the circle will be the midpoint of the diameter's endpoints.

midpoint = ( average of the x's , average of the y's )

midpoint = ( \(\frac{-10+4}{2} , \frac{-2+6}{2}\) )

midpoint = ( -3 , 2 )

 

b.

The radius will be the distance from the midpoint to an endpoint of the diameter. We can use the distance formula to find this distance.

radius = \(\sqrt{(x_1-x_2)^2+(y_1-y_2)^2}\)

radius = \(\sqrt{(-3-(-10))^2+(2-(-2))^2}\)

radius = \(\sqrt{49+16}\)

radius = \(\sqrt{65}\)

 

c.

The equation of a circle is (x - h)2 + (y - k)2 = r2

Where ( h, k ) is the center point, and r is the radius.

 

Just plug in the center point and radius into the equation.

(x + 3)2 + (y - 2)2 = 65

hectictar  Apr 11, 2017
 #2
avatar+2509 
+1

thanks!

NotSoSmart  Apr 11, 2017

13 Online Users

New Privacy Policy

We use cookies to personalise content and advertisements and to analyse access to our website. Furthermore, our partners for online advertising receive information about your use of our website.
For more information: our cookie policy and privacy policy.